2010
DOI: 10.1111/j.1475-097x.2010.00925.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation and reliability of ultrasonographic quantification of the architecture of the medial gastrocnemius muscle in young children

Abstract: The aim of this study was to evaluate the suitability of ultrasonography for the quantification of gastrocnemius muscle architecture in healthy young children. The variation and reliability of measurement of muscle thickness, pennation angle and fibre length of the medial gastrocnemius were determined, using stationary and portable ultrasound machines, in 13 boys and eight girls aged 4-10. Ultrasound images were obtained from each leg, in duplicate, with the ankle at 90 degrees , then at maximal plantar flexio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
74
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(88 citation statements)
references
References 34 publications
(154 reference statements)
11
74
1
2
Order By: Relevance
“…The authors alerted that this structure has been neglected and showed that the superficial fascicles are significantly smaller than the deepest ones. We estimated the fascicle length using trigonometric extrapolation as others (Blazevich et al, 2006;Legerlotz et al, 2010), which assumes that the fascicles are linear, ignoring the curvilinear arrangements (Noorkoiv et al, 2010). This could have resulted in underestimated semitendinosus fascicle length.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors alerted that this structure has been neglected and showed that the superficial fascicles are significantly smaller than the deepest ones. We estimated the fascicle length using trigonometric extrapolation as others (Blazevich et al, 2006;Legerlotz et al, 2010), which assumes that the fascicles are linear, ignoring the curvilinear arrangements (Noorkoiv et al, 2010). This could have resulted in underestimated semitendinosus fascicle length.…”
Section: Discussionmentioning
confidence: 99%
“…The architecture parameters can be well visualized by ultrasound at rest or during contraction (Gomes et al, 2010;Martins et al, 2012;Potier et al, 2009;Timmins et al, 2015). The reliability of muscle architecture measurements assessed using ultrasound is reported in many studies with different methodologies involving repeated measures between images, sessions, and raters (Legerlotz et al, 2010;Lima et al, 2012). These studies have been important to determine a reproducibility of muscle architecture parameters which are measured very often in training and rehabilitation protocols.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported estimates of reliability were good to high. [13][14][15][16][17][18][19][20][21] With the exception of a study reported by Thoirs and Englsh, 15 the reported intrarater correlation coefficients (ICC) among studies ranged between 0.90 and 0.99. Thoirs and Englsh 15 reported that high test-retest reliability was indicated in the lower extremity when subjects were measured in a standing position (ICC, 0.70-0.89; 95% confidence interval (CI), 0.79-0.94 for anterior thigh and 0.49-0.84 for posterior thigh, respectively).…”
Section: Validity and Reliability Of Mt Measurementsmentioning
confidence: 99%
“…Based on their functional roles, as a musculotendinous unit, in the mechanics of human bipedalism and their significance in the clinical assessment of muscle wasting in children, adolescents and adults [21][22][23]; in the occurrence of overuse injuries of the foot [24], it is absolutely necessary to document a nomographic data of their thickness, to serve as a good guidepost to the further understanding of their biomechanics especially, in a Sub-Saharan African population where studies on the structural disposition of muscles are absolutely lacking. The study will also form a possible basis for description of racial/ethnic differences as was described by Ishida et al [25] between Japanese and Americans; and sexual dimorphism.…”
Section: Introductionmentioning
confidence: 99%